Direct anterior total hip arthroplasty: a retrospective study - Trivellin, Giacomo; Assaker, Assad; Vacchiano, Andrea; Cominelli, Dario; Meyer, Andrea (Acta Biomedica Atenei Parmensis, 2020)
Background: The quest for less invasive surgical approaches for total hip arthroplasty has gained much attention recently. There is very little information regarding differences about the main surgical access. The purpose of this study was to collect data regarding patients’ subjective perceptions of the direct anterior hip arthroplasty, heterotopic ossification degrees, range of movement and complication and comparing these satisfaction results with the other surgical techniques. Methods: The study involved 51 patients operated in our Orthopedic clinic with direct anterior total hip arthroplasty between 2016 and 2017. We recorded and compared clinical and radiographic data at 1 year with anterolateral hip arthroplasty. Result: Only one patient described less than an 8/10 satisfaction; 5.45% of the patients restored the physiological ROM and 21.82 % lost only 5° of range of motion. According to Brooker Classification 58.33 % did not develop any Heterotopic Ossification. Conclusion: All standard approaches to the hip have been shown to be safe and efficacious, with particular advantages and disadvantages for each approach. DAA has some short term advantages like a faster recovery, less blood loss and less heterotopic ossification. Long term studies are required to demonstrate a cost benefit or quality of care advantage to other hip approaches.